Molecular assembly of a pyridine functionalized janusarene - Yin, Zhibo; Fan, Luoyi; Lin, Chaojun; Shi, Haonan; Xiong, Bangyuan; Gu, Jiajian; Zhu, Yanpeng; Wang, Jiaobing (Chinese chemical letters, 2022)
We describe a janusarene derivative PyJ, which forms micrometer-scale one-dimensional metallo-supramolecular polymer through coordination driven self-assembly. PyJ is a well-preorganized dodecatopic pyridyl ligand built on a hexaphenylbenzene platform. The two-face structural feature of PyJ allows for a delicate control over multiple Py-Ag+-Py coordination interactions, leading to assembled structure of PyJ-Ag+, which was characterized by dynamic light scattering, atomic force microscopy, and transmission electron microscopy. This work describes a pyridine functionalized janusarene derivative PyJ, which forms micrometer-scale one-dimensional metallo-supramolecular polymer through coordination driven self-assembly. [Display omitted]